25 days 'til Christmas - Alexander, Poppy (Willaim Morrow, 2019)
Kate Potter used to love Christmas. A few years ago, she would have been wrapping her presents in September and baking mince pies on Halloween, counting down the days and hours to Christmas. But that was before Kate's husband left for the army and never came home. Now she can hardly stand December at all. Kate can't deny she's lonely, yet she doesn't think she's ready for romance. She knows that her son, Jack, needs a Christmas to remember--just like Kate needs a miracle to help her finally move forward with her life. So she's decided if there isn't a miracle on its way, she'll just have to make her own. As Kate's advent countdown to the best Christmas ever begins, she soon realizes that even with the best laid plans, you can't plan for the unexpected. For when the path of the loneliest woman in town crosses with that of the loneliest man, these two destined hearts might find a way to save the holiday for both of them.